ARTIKEL REVIEW : SISTEM IMUNITAS DALAM KEHAMILAN - Made Tangkas (ARCHIVE OF COMMUNITY HEALTH, 2023)
Pregnancy is the process of continuing the existence of an organism, and preventing its extinction. During pregnancy, there is a fundamental human adaptation process that increases the body's resistance to the risk of external attack. Regardless of the role of the immune system in early pregnancy, an increase in the human immune system, which is the most important system for dealing with infections to protect the mother and the fetus, is one of the important adaptation responses to protect the mother as well as the fetus. Various physiological changes are interrelated, especially to ensure the growth of the baby in the uterus can take place properly. Anatomical, physiological and biochemical adaptations in pregnancy are profound. Many significant changes occur immediately after fertilization and continue throughout pregnancy and most occur in response to physiological stimulation by the baby and placenta. This article discusses the changes in immune system function involved in pregnancy. Keywords: immune system, pregnancy adaptation, pro-inflammatory and anti-inflammatory responses